Reading literacy strategies in public speaking performance: A study of first-year students at SMK Miftahul Qulub: Reading literacy strategies in public speaking performance: A study of first-year students at SMK Miftahul Qulub - Rahmawati, Mila; Arifin Alatas, Mochamad (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
Reading literacy, as a cornerstone of intellectual and communicative development, plays a crucial role in shaping students’ ability to express ideas effectively and confidently in public contexts. This study explores how reading literacy strategies contribute to the enhancement of students’ public speaking skills at SMK Miftahul Qulub. Using a descriptive qualitative approach, data were obtained through observations, interviews, and documentation of literacy and speaking activities. The findings indicate that the integration of reading, discussion, and structured speech preparation enables students to build critical thinking, expand vocabulary, and improve coherence in speech delivery. Reading literacy also strengthens students’ confidence and self-expression, allowing them to articulate ideas with greater fluency and reflective depth. The study concludes that literacy serves as both a cognitive and affective foundation for public speaking, supporting the development of communicative competence and creative expression. Therefore, schools are encouraged to embed literacy-based practices within language learning programs to foster students’ holistic personal and academic growth.